Vitamin D levels and parathyroid hormone variations of children living in a subtropical climate: a data mining study - Ozlem Naciye Sahin; Muhittin Serdar; Mustafa Serteser; Ibrahim Unsal; Aysel Ozpinar (BMC, 2018)
Abstract Background Vitamin D and intact parathyroid hormone (iPTH) play a crucial role in calcium homeostasis and bone health of children. Serum level of 25-hydroxyvitamin D (25-OHD) is considered to be the most accurate marker for vitamin D status. However, there have only been a few studies, with limited number of subjects, investigating the relationship between 25-OHD and parathyroid hormone (PTH) in children. The aim of this study was to evaluate the seasonal 25-OHD levels and its associations with intact parathyroid hormone (iPTH) in Turkish children at all pediatric ages; and then to define a critical decision threshold level for 25-OHD deficiency in Turkish children. Methods A retrospective record review of 90,042 children, was performed on serum 25-OHD and for 3525 iPTH levels. They were measured by mass spectrometry method and by electrochemiluminescence immunoassay simultaneously. Results 25-OHD levels showed a sinusoidal fluctuation througout the year; being significantly higher in summer and autumn (p < 0,01). 25-OHD levels decreased with respect to age. The significant inverse relationship that was found between iPTH and 25-OHD suggests that the inflection point of serum 25-OHD level for maximal suppression of PTH is at 30 ng/ml. Conclusion As the rate of vitamin D deficiency decreases in the early years due to vitamin D supplementation, the recommendation should be set due to a clinical threshold level of 30 ng/ml for 25-OHD based on PTH levels in children of our population.